The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1182/blood-2016-11-745638
|View full text |Cite
|
Sign up to set email alerts
|

Reticular dysgenesis: international survey on clinical presentation, transplantation, and outcome

Abstract: Reticular dysgenesis (RD) is a rare congenital disorder defined clinically by the combination of severe combined immunodeficiency (SCID), agranulocytosis, and sensorineural deafness. Mutations in the gene encoding adenylate kinase 2 were identified to cause the disorder. Hematopoietic stem cell transplantation (HSCT) is the only option to cure this otherwise fatal disease. Retrospective data on clinical presentation, genetics, and outcome of HSCT were collected from centers in Europe, Asia, and North America f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 18 publications
1
47
1
Order By: Relevance
“…Additionally, a markedly reduced expression of the erythroid marker hbae1.1 was noted, supporting the idea that erythropoiesis defects are intrinsic to Ak2 deficiency in this model. The observation of a large fraction of anaemic RD patients at birth complements these observations (Hoenig et al , ). Furthermore, Rissone et al () showed that increased oxidative stress and reactive oxygen species (ROS) production results in cell death and apoptosis and that Ak2 deficiency causes a progressive reduction of haematopoietic stem and progenitor cells by this mechanism.…”
Section: Pathophysiology Of Ak2 Deficiency In Cellular and Animal Modelssupporting
confidence: 76%
See 2 more Smart Citations
“…Additionally, a markedly reduced expression of the erythroid marker hbae1.1 was noted, supporting the idea that erythropoiesis defects are intrinsic to Ak2 deficiency in this model. The observation of a large fraction of anaemic RD patients at birth complements these observations (Hoenig et al , ). Furthermore, Rissone et al () showed that increased oxidative stress and reactive oxygen species (ROS) production results in cell death and apoptosis and that Ak2 deficiency causes a progressive reduction of haematopoietic stem and progenitor cells by this mechanism.…”
Section: Pathophysiology Of Ak2 Deficiency In Cellular and Animal Modelssupporting
confidence: 76%
“…Upon differentiation, fibroblast‐derived induced pluripotent stem cells (iPSCs) from an AK2‐deficient patient recapitulated the promyeloid block that can be observed in the bone marrow of patients (Lagresle‐Peyrou et al , ; Hoenig et al , ). This block is imitated in colony‐forming assays with bone marrow mononuclear cells originating from RD patients (Lagresle‐Peyrou et al , ).…”
Section: Pathophysiology Of Ak2 Deficiency In Cellular and Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although long-term survival after HCT was 68%, graft failure or persistence/recurrence of agranulocytosis was the predominant cause of treatment failure. 1 Myeloablative transplant conditioning regimens and transplantation of T-cell-replete grafts were associated with best outcomes.…”
mentioning
confidence: 99%
“…1 The SCIDs are phenotypically and genotypically heterogeneous, and RD is considered 1 of the most severe forms. 2,3 RD is inherited as an autosomal recessive disorder and accounts for ,2% of SCID and classed as T-, B-, and natural killer-deficient SCID.…”
mentioning
confidence: 99%